Kesadaran, Motivasi dan Niat Remaja Terhadap Kehamilan Tidak Diinginkan di SMA Negeri 1 Nekamese. Kabupaten Kupang - Delice Vebrida Pobas; Imelda Manurung; Anderias Umbu Roga; Marni Marni; Sintha Purimahua (Jurnal Ners, 2026)
Unwanted teenage pregnancy refers to a pregnancy that occurs when a teenager (typically aged 10–19 or 15–19, depending on the study’s definition) did not intend or plan to become pregnant at the time of conception. This phenomenon is not merely a medical issue—it is a social, economic, and educational problem because its consequences are often long-term for adolescents, the child born, families, and society. Many adolescent pregnancies occur in contexts where access to reproductive health education, contraceptive services, and social protection remains limited; social factors such as poverty, gender norms, early marriage, and peer pressure also play a significant role. Individual awareness of the risks and consequences of unintended pregnancy plays a crucial role in shaping preventive behavior. Motivation can be defined as an internal drive within a person to act and behave. Motivation can also be defined as a need—a potential within a person that requires a response. Intention describes an individual’s readiness to act. This study employs a qualitative approach with a phenomenological design. This approach was chosen because the research focuses on a deep understanding of adolescents’ subjective experiences regarding their motivation, intention, and perceptions of unintended pregnancy. Research data were collected from 10 female respondents at State High School 1 Nekamese, Kupang District. Ratings provided by respondents to assess adolescents’ awareness, motivation, and intentions regarding unintended pregnancy. This study involved primary respondents, peers, and guidance counselors. The study was conducted to assess the influence of parents, peers, and teachers on adolescents’ motivation and intentions to prevent unintended pregnancy at State High School 1 Nekamese, Kupang Regency.